Fundamentals of electromagnetics with MATLAB - Lonngren, Karl E., (Karl Erik), 1938-; Savov, Sava Vasilev; Jost, Randy J. (Raleigh, NC : SciTech Pub.)
Includes bibliographical references (p. 490-492) and index